种无土栽培营养液多级循环利用装置 (2019)
本发明公开了种无土栽培营养液多级循环利用装置,克服了传统雾培方式能源和资源投入较高，而废弃营养液盐分较高,存在环境污染的问题，其包括雾培装置、营养液缓冲箱、二级供液电磁阀、岩棉培装置、PH传感器、EC传感器、臭氧发生器、母液控制电磁阀、母液箱、潜水泵、营养液池与控制中心。潜水泵和雾培装置管连接，雾培装置和营养液缓冲箱管连接，营养液缓冲箱和岩棉培装置管连接，营养液缓冲箱和岩棉培装置之间的管道上安装有二级供液电磁阀，岩棉培装置和营养液池管连接，母液箱和营养液池连接的管道上安装母液控制电磁阀，PH传感器和EC传感器置于营养液池内并分别与控制中心电线连接，臭氧发生器置于营养液池外并与营养液池管连接。 The invention discloses a multistage cyclic utilization device for a soilless culture nutrient solution. The multistage cyclic utilization device is used for overcoming the problems of the traditional spray-culture mode that the investment of energy sources and resources is relatively big and the waste nutrient solution is relatively high in salt content and causes environmental pollution. The multistage cyclic utilization device spray-culture devices, a nutrient solution buffering tank, second-stage solution supplying electromagnetic valves, rock wool culture devices, a pH sensor, an EC sensor, an ozone generator, stock solution controlling electromagnetic valves, stock solution tanks, a submersible pump, a nutrie